Enamel surface roughness after orthodontic adhesive removal: an in vitro study comparing four clearance methods - Denisa Raticová; Magadalena Koťová; Aleš Bezrouk; Leo Sala; Petra Křížová; Leger Aleš; Wanda Urbanová (European Oral Research)
Purpose: Adhesive remnants removal is the last key step influencing orthodontic treatment outcomes. Four different clearance methods (CM) of orthodontic adhesive were evaluated to determine, which achieved the smoothest enamel surface in the shortest time.Materials and Methods: 75 intact premolars extracted for orthodontic purposes were included, sixty had an orthodontic bracket bonded and subsequently removed, and fifteen served as the control group. Four CMs were used to clear the tooth surface of 15 premolars each: carbide bur (CB), carbide bur with titanium nitride surface treatment + fine carbide bur (CBCB), glass fiber-reinforced composite instrument (GFCB), zirconia bur + glass fiber-reinforced composite bur (ZBCB). The processing time was recorded. In ten premolars from each group, the enamel surface was evaluated by atomic force microscopy estimating mean roughness (Ra), roughness profile value (Rq), and roughness depth (Rt). Enamel Damage Index (EDI) was assessed with a scanning electron microscope on 5 remaining premolars.Results: Significant differences were observed in all evaluated parameters - Ra (p<0.0001), Rq (p<0.0001), and Rt (p<0.0001). GFCB exhibited the smoothest surface in all parameters. The lowest EDI exhibited teeth treated by GFCB, however, the differences were not significant. Working with GFCB took the longest time (mean 116s), and the shortest with CBCB (mean 49s).Conclusion: Using CB is the fastest clearance method, but the enamel surface roughness was highest. Clearing with a set of instruments CBCB proved to be a fast method with satisfying remaining enamel roughness.